Theoretical modeling of longitudinal piezoelectric characteristic for cellular polymers. Issue 1 (January 2022) - Najihi, Ikrame; Ennawaoui, Chouaib; Hajjaji, Abdelowahed; Boughaleb, Yahia
Efficient energy harvesting is a difficult challenge that consists in the development of systems allowing charging autonomous and low-power devices. In addition to traditional piezoelectric polymers, mono-crystals, and ceramics, cellular electrets offer consistent solutions by converting wasted vibration energy from the environment to usable electrical energy. This paper presents an electromechanical model to study the energy harvesting capability of cellular polymers. The theoretical study models the response of these materials to investigate the effect of different parameters on the piezoelectric coefficient d33, particularly. The model considers the percentage of porosity, surface charge density in each polymer–gas surface, the properties of the polymer matrix and the gas encapsulated in the pores, and the Young's modulus of the porous film. For poly(ethylene-co-vinyl acetate), the results showed that the piezoelectric performance of the film declines with the increase of the film thickness. However, the variation of the d33 as a function of the percentage of porosity is exponential and can achieve 4.24 pC/N for a porosity of 80%. Compared to a previously published experiment, the theoretical results have proven a good agreement with only 3.3% error.